Cities and biodiversity: Perspectives and governance challenges for implementing the convention on biological diversity (CBD) at the city level - Puppim de Oliveira, J; Balaban, O; Doll, C; Moreno-Peñaranda, R; Gasparatos, A; Iossifova, D; Suwa, A (2011)
City governments are fundamental to implement international environmental agreements, such as the convention on biological diversity (CBD). Even though many of them are not directly involved in the negotiation of international agreements, which are signed by national governments, most of those agreements are in fact implemented at the city level. The importance of city governance to tackle the challenges of biodiversity loss has increased as urban population has grown enormously in the last decades, particularly in developing countries. The way cities are designed, planned and governed influences the magnitude of their direct and indirect impacts on biodiversity.This paper analyzes the relationship between cities, local governance and biodiversity. Initially, we examine the relationships between cities and biodiversity by looking at the major influences cities have on biodiversity loss or conservation within and outside the city boundaries, as well as the benefits of biodiversity conservation to cities, such as the provision of ecosystem services. The paper then moves to understand what are the main urban processes and governance mechanisms that can be improved to make cities effective to implement the directives of the CBD.Urbanization creates new challenges for biodiversity conservation. As a large part of the world's population moves from rural to urban areas, there are changes in the link between human activities and biodiversity, and consequently to the way we should think biodiversity conservation policies. However, scarce attention has been given to understand how to make cities more biodiversity friendly, both within the urban fabric, but particularly in faraway places. © 2010 Elsevier Ltd.